'Don't judge me': narratives of living with FGM - McGarry, Julie; Recchia, Natasha (Emerald, 2017)
Purpose: To facilitate a participant led arts based workshop survivors of FGM in order to explore their experiences and impact of FGM on health and wellbeing. To use the artefacts to inform development of an e-learning resource. Design/methodology/approach: The study utilised a creative narrative approach which included the sharing of personal stories, the creation of pottery models and the sharing of artefacts. A narrative approach was chosen as the methodology for the study as narratives are now well established within qualitative research as a meaningful way in which the voices of participants take precedence over those of the researcher. Six women who are living with FGM agreed to take part. Findings: The composition of the workshop essentially encompassed two main strands i) the creation of a persona and ii) sharing artefacts. These are described in detail with supplementary images included as appropriate. We have not attempted to present the findings of the workshop from the perspective of the researcher but have rather enabled the findings to speak for themselves. Research limitations/implications: There is a paucity of studies which have explored women experiences of living with FGM and the impact on health and wellbeing. The findings suggest that there is further scope for research and practice development which examines the impact of education on professional’s approaches to FGM. Practical implications: Social implications: Originality/value: This study and the wider focus towards the impact of FGM beyond the physical or procedural aspects of FGM offer a contribution to the evolving evidence base in this field.